Regulating Access to International Large-Value Payment Systems - Holthausen, Cornelia; Rønde, Thomas (Review of Financial Studies, 2002)
This article studies access regulation to international large-value payment systems when banking supervision is national. We focus on the choice between net and real-time gross settlement. As a novel feature, the communication between the public authorities is endogenized. It is shown that the national authorities’ incentives are not perfectly aligned concerning the settlement method. Therefore public regulation fails to implement the first-best access criteria. Banks prefer net settlement too often due to limited liability. Still, if banks have superior information about their counterparties, private involvement in access regulation is desirable as it reveals information to the public authorities.